Collisional-Radiative Calculations of Optically Thin and Thick Plasmas Using the Computational Package ABAKO/RAPCAL (Communications in Computational Physics, 2010)
Non-local thermodynamic equilibrium (NLTE) conditions are universal inlaboratory and astrophysical plasmas and, for this reason, the theory of NLTE plasmasis nowadays a very active subject. The populations of atomic levels and radiativeproperties are essential magnitudes in the study of these plasmas and the calculationof those properties relies on the so-called collisional-radiative (CR) models. However,the complexity of these models has led to the development of numerous collisional-radiativecodes and this is a current research topic in plasmas. In this work is presenteda versatile computational package, named ABAKO/RAPCAL, to calculate thepopulations of atomic levels and radiative properties of optically thin and thick, low-to-highZ, NLTE plasmas. ABAKO/RAPCAL combines a set of analytical approximationswhich yield substantial savings in computing running time, still comparingwell with more elaborated codes and experimental data. In order to show the capabilitiesof the code and the accuracy of its results, calculations of several relevant plasmamagnitudes for various plasma situations are shown and compared.